Pengaruh Dosis Pupuk NPK Pelangi dan Pewiwilan Terhadap Pertumbuhan dan Produksi Tanaman Terung (Solanum melongena L.) - Arief Setiawan; Tutik Nugrahini; Mahdalena Mahdalena (Universitas Widya Gama Mahakam, 2016)
Dose Effect of NPK fertilizer and Pewiwilan To Growth And Production Plant eggplant (S. melongena L.). The purpose of this study was to determine the effect of administered dose of NPK fertilizer and Pewiwilan on the growth and yield of eggplant (S. melongena L.). This research was conducted in L2 Block C Karang Single District of Tenggarong Seberang Kutai regency, which was conducted over four months from seedling to harvest, ie from April to August 2015dengan using a randomized block design (RAK) with factorial 4 X 2 each treatment was repeated four times, the first factor is dosage NPK fertilizer (P), which consists of 4 levels, namely: p0 (control), p1 (15 grams / plant), p2 (20 grams / plant), p3 ( 25 grams / plant). The second factor is Pewiwilan (W) consisting of two levels ie: w0 (without cut), w1 (with cut). Results from the study showed that the treatment dose of NPK fertilizer (P) did not significantly affect plant height age of 20 days after planting and the number of branches of productive age of 50 and 70 days after planting. But very significant effect on plant height, aged 30, 50, and 70 days after planting and the age of the plant when the first harvest, planting fruit number and weight of the fresh fruit crop. Average yields are best demonstrated by the treatment p3 (25 grams / plant). While treatment Pewiwilan (W) showed no significant effect on plant height was 20, 30, 50, and 70 days after planting, the number of branches of productive ages of 50 and 70 days after planting, as well as the age of the plant when harvested the first time, the number of fruit crops and weight fresh fruit planting. Interaction doses of NPK Pelangi and Pewiwilan not significantly affect plant height was 20, 30, 50, and 70 days after planting, the number of branches of productive ages of 50 and 70 days after planting, as well as the age of the plant when harvested the first time, the number of fruit crops and fresh fruit heavy cropping